Janus single-layer group-III monochalcogenides: a promising visible-light photocatalyst. (23rd August 2019) - Yang, Hongchao; Zhao, Pei; Ma, Yandong; Lv, Xingshuai; Huang, Baibiao; Dai, Ying
Abstract: Single-layer group-III monochalcogenides are promising candidate materials for a great range of applications in both material science and device physics. Herein, we propose a novel family of Janus single-layer group-III monochalcogenides (J-MX, J  =  Ga, M  =  In, X  =  S and Se) using first-principles calculations. We find that these structures exhibit excellent stability as well as high experimental feasibility. Their band gaps can be tuned effectively by external electric field, while the morphologies of band structures changed little. Importantly, their suitable band gaps (2.07 eV–2.60 eV) and band edge positons enable them promising candidates in photocatalytics. Moreover, the compressive strain can further make the band edge positions match with the redox potentials of water splitting better, and hence can increase the efficiency of solar energy conversion. The adsorption of H adatoms on the S surface and decomposition of H2 O on the Se surface of InSe–GaS is further investigated to reveal the microscopic mechanism of water splitting. Our works provide a novel family of promising photocatalytic materials.